2017
DOI: 10.3390/ijgi6030060
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study Investigating Gender Effects on Using 3D Maps for Spatial Orientation in Wayfinding

Abstract: 3D representations in applications that provide self-localization and orientation in wayfinding have become increasingly popular in recent years because of technical advances in the field. However, human factors have been largely ignored while designing 3D representations in support of pedestrian navigation. This exploratory study aims to explore gender effects on using 3D maps for spatial orientation. We designed a 3D map that combines salient 3D landmarks and 2D layouts, and evaluated gender differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 84 publications
2
26
0
Order By: Relevance
“…Therefore, the Label AOIs have a higher degree of recognition [56] and are more likely to be regarded as landmarks. This finding is consistent with that of Liao and Dong [57], who found that displaying 3D models, which are more salient than 2D maps, can improve map usability for male users. In general, rich label information should be provided for ORI and SRS tasks, and navigation systems should highlight the label information, for example, by using larger annotation or bright colours.…”
Section: Performance On Road and Label Aoissupporting
confidence: 91%
“…Therefore, the Label AOIs have a higher degree of recognition [56] and are more likely to be regarded as landmarks. This finding is consistent with that of Liao and Dong [57], who found that displaying 3D models, which are more salient than 2D maps, can improve map usability for male users. In general, rich label information should be provided for ORI and SRS tasks, and navigation systems should highlight the label information, for example, by using larger annotation or bright colours.…”
Section: Performance On Road and Label Aoissupporting
confidence: 91%
“…Street View application provides an immersive experience, and has been used in wayfinding spatial orientation research for educational purposes [12,37]. This kind of three-dimensional immersive representation is close to the real environment, and allows wayfinders to look around for visual cues to orient themselves.…”
Section: Virtual Immersive Environments With Google Street View Geospmentioning
confidence: 99%
“…The design of the experiment was based on previous experiments carried out by Lynch [2], MacEachren [51] and Liao and Dong [12] in the field of spatial orientation in wayfinding. Participants learned a route from point A to point B on a 2D map in an urban environment, and then performed this wayfinding task (to go from A to B) in a 3D immersive environment.…”
Section: Experiments Designmentioning
confidence: 99%
“…Students can also "color" their rocket, which enhances the visibility of the launch, much as in the real world. Controls were placed on the left hand side of the screen where they were always visible (Liao 2017). Making the variables readily visible and the simulation was easily usable (Rose 2017).…”
Section: Stock Et Al (Stock 2008) Established Three Categories Of VImentioning
confidence: 99%